2019
DOI: 10.1016/j.isci.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Biased Signaling of the Mu Opioid Receptor Revealed in Native Neurons

Abstract: G protein-coupled receptors are key signaling molecules and major targets for pharmaceuticals. The concept of ligand-dependent biased signaling raises the possibility of developing drugs with improved efficacy and safety profiles, yet translating this concept to native tissues remains a major challenge. Whether drug activity profiling in recombinant cell-based assays, traditionally used for drug discovery, has any relevance to physiology is unknown. Here we focused on the mu opioid receptor, the unrivalled tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 35 publications
5
73
0
Order By: Relevance
“…When considering βarrestin recruitment to the PM upon receptor stimulation, our analysis shows that 22% of receptors did not recruit βarrestin beyond the established threshold, even in the presence of overexpressed GRK2, which is known to favor recruitment (Ehrlich et al, 2019) (Figure 4E). Among the receptors able to recruit arrestins, only a very small number of receptors selectively recruited either βarrestin1 (1.3%) or βarrestin2 (6.4%), most of them recruiting both βarrestin subtypes in the presence of GRK2 (92.3%) ( Figure 4E).…”
Section: Diversity Of Coupling Selectivity Between G Protein Familiesmentioning
confidence: 94%
“…When considering βarrestin recruitment to the PM upon receptor stimulation, our analysis shows that 22% of receptors did not recruit βarrestin beyond the established threshold, even in the presence of overexpressed GRK2, which is known to favor recruitment (Ehrlich et al, 2019) (Figure 4E). Among the receptors able to recruit arrestins, only a very small number of receptors selectively recruited either βarrestin1 (1.3%) or βarrestin2 (6.4%), most of them recruiting both βarrestin subtypes in the presence of GRK2 (92.3%) ( Figure 4E).…”
Section: Diversity Of Coupling Selectivity Between G Protein Familiesmentioning
confidence: 94%
“…The involvement of µ-OR phosphorylation in these processes was confirmed by later studies 10,[21][22][23][24] . In addition to GRK2, in vitro studies have shown that GRK3/5/6 have direct roles in µ-OR phosphorylation and/or internalization 16,23,[25][26][27] . Moreover, studies have also utilized phospho-site specific antibodies to demonstrate that the µ-OR is differentially phosphorylated by distinct GRK isotypes depending on the agonist used.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that MOR regulation is strongly agonist dependent and it can be argued that in the present study, we used morphine, which has low affinity for β-arresin-2, to demonstrate that opioid tolerance in the small intestine is β-arrestin-2-independent. However, we have previously shown that tolerance in the isolated ileum develops to repeated exposure of high efficacy opioid agonists like fentanyl or etorphine, known to engage β-arrestins with high affinity (McPherson et al, 2010;Maguma et al, 2012;Ehrlich et al, 2019). Consequently, the β-arrestin-2-independent mechanism of tolerance in the ileum is not contingent on the opioid agonist.…”
Section: Discussionmentioning
confidence: 99%